Metabolic profiles of planktonic and biofilm cells of Candida orthopsilosis - Pires, Regina Helena [UNESP]; Cataldi, Thaís Regiani; Franceschini, Livia Maria; Labate, Mônica Veneziano; Fusco-Almeida, Ana Marisa [UNESP]; Labate, Carlos Alberto; Palma, Mario Sérgio [UNESP]; Soares Mendes-Giannini, Maria José [UNESP] (Taylor & Francis, 2016)
Aim: This study aims to understand which Candida orthopsilosis protein aids fungus adaptation upon its switching from planktonic growth to biofilm. Materials & methods: Ion mobility separation within mass spectrometry analysis combination were used. Results: Proteins mapped for different biosynthetic pathways showed that selective ribosome autophagy might occur in biofilms. Glucose, used as a carbon source in the glycolytic flux, changed to glycogen and trehalose. Conclusion: Candida orthopsilosis expresses proteins that combine a variety of mechanisms to provide yeasts with the means to adjust the catalytic properties of enzymes. Adjustment of the enzymes helps modulate the biosynthesis/degradation rates of the available nutrients, in order to control and coordinate the metabolic pathways that enable cells to express an adequate response to nutrient availability.
Keywords: biofilms; Candida orthopsilosis; metabolic pathways; proteome